A cointegration panel data analysis for international R&D spillovers and R&D cooperation: case study for Mediterranean countries. (3rd January 2012) - Sadraoui, Tarek
In this paper, we consider R&D cooperation and direct foreign investment as a channel of international spillovers by an empirical literature on innovation and growth. First, spillovers are limited to the country where R&D is conducted; the growth rate in each country will be determined by the country's own R&D-efforts and by R&D cooperation ignored a long time in growth literature. Second, spillovers take place across borders, and growth rates will tend to converge across countries. Two potential channels for R&D spillovers are examined: localisation of FDI and R&D cooperation. In examining these issues, panel data for six Mediterranean countries will be used over the period 1970 to 2008.